2014
DOI: 10.1186/1757-4749-6-18
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between Campylobacter and Helicobacter species and other gastrointestinal microbiota of commercial broiler chickens

Abstract: BackgroundPoultry represent an important source of foodborne enteropathogens, in particular thermophilic Campylobacter species. Many of these organisms colonize the intestinal tract of broiler chickens as harmless commensals, and therefore, often remain undetected prior to slaughter. The exact reasons for the lack of clinical disease are unknown, but analysis of the gastrointestinal microbiota of broiler chickens may improve our understanding of the microbial interactions with the host.MethodsIn this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 48 publications
13
97
2
3
Order By: Relevance
“…This confirms data from an earlier study in which a positive correlation between high levels of Clostridium perfringens (>6 log) and the colonization of C. jejuni were found by real-time quantitative PCR (Skånseng et al, 2006; Thibodeau et al, 2015). This might be due to the fact that C. jejuni acts as a hydrogen sink leading to improved growth conditions for some Clostridia through increased fermentation (Kaakoush et al, 2014). This link can also be explained by the fact that the Clostridium organic acid production could be used by C. jejuni as an energy source.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms data from an earlier study in which a positive correlation between high levels of Clostridium perfringens (>6 log) and the colonization of C. jejuni were found by real-time quantitative PCR (Skånseng et al, 2006; Thibodeau et al, 2015). This might be due to the fact that C. jejuni acts as a hydrogen sink leading to improved growth conditions for some Clostridia through increased fermentation (Kaakoush et al, 2014). This link can also be explained by the fact that the Clostridium organic acid production could be used by C. jejuni as an energy source.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in mice demonstrated that a diet-induced alteration of the intestinal microbiota, comprising an increase in the abundance of E. coli and a decrease in Lactobacillus was associated with a greater susceptibility to C. jejuni infection (Bereswill et al, 2011). Furthermore, another study reported an association between higher C. jejuni counts and lower abundance of Lactobacillus (Kaakoush et al, 2014). The same research group showed that not only Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Hilbert et al, 2010; Haag et al, 2012; Dicksved et al, 2014; Kaakoush et al, 2014) have shown that Campylobacter closely interacts with other microorganisms, the intestinal microbiota is important for Campylobacter colonization in chickens (Kaakoush et al, 2014) and Campylobacter colonization leads to a change in the intestinal microbiota (Haag et al, 2012). According to another recent study (Sofka et al, 2015), the caecal microbiota in Campylobacter -free and Campylobacter colonized chickens differed considerably.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chickens, commercial turkeys and ducks can also serve as reservoirs of C. jejuni and C. coli (315)(316)(317). Furthermore, poultry is also an important reservoir of other Campylobacter species, such as C. lari, C. upsaliensis, and C. concisus (318,319). Domesticated broiler chickens and imported chickens both contribute to the overall burden of Campylobacter infections (320).…”
Section: Poultrymentioning
confidence: 99%